Small states and hegemonic competition in Southeast Asia pursuing autonomy, security and development amid great power politics - Tang, Chih-Mao (Routledge advances in international relations and global politics, 2018)
In the last few decades, Southeast Asia has become generally more peaceful and more prosperous, with progress in economic development, regional cooperation and integration. ASEAN in particular plays a leading role within and beyond the region in promoting multilateral cooperation in both security and economic matters. Drawing on the ideas of power transition theory and recent works of capitalist peace, Tang argues that small states can exploit the competition between great powers to make economic gains and ensure security while maintaining their autonomy.